Variations in Soil Functional Fungal Community Structure Associated With Pure and Mixed Plantations in Typical Temperate Forests of China - Wu, Di; Zhang, Mengmeng; Peng, Mu; Sui, Xin; Li, Wei; Sun, Guangyu (Frontiers in Microbiology, 2019)
Forest plants are in constant contact with the soil fungal community, which plays an important role in the circulation of nutrients through forest ecosystems. The objective of this study was to evaluate the fungal diversity in soil and elucidate the ecological role of functional fungal communities in forest ecosystems using soil samples from seven different plantations in northeastern China. Our results showed that the fungal communities were dominated by the phyla Ascomycota, Basidiomycota, and Mortierellomycota, and the mixed plantation of Fraxinus mandshurica and Pinus koraiensis had a soil fungal population clearly divergent from those in the other plantations. Additionally, the mixed plantation of F. mandshurica and P. koraiensis, which was low in soil nutrients, contained a highly diverse and abundant population of ectomycorrhizal fungi, whereas saprophytic fungi were more abundant in plantations with high soil nutrients. Redundancy analysis demonstrated a strong correlation between saprophytic fungi and the level of soil nutrients, whereas ectomycorrhizal fungi were mainly distributed in soils with low-nutrient. Our findings provide insights into the importance of functional fungi and the mediation of soil nutrients in mixed plantations and reveal the effect of biodiversity on temperate forests.